Wizerunek kobiety w "Eklodze II" Nemezjana - Kucz, Anna (Collectanea Philologica, 2021)
The aim of the article is to analyse the image of a woman in the II Eclogue written by Nemesianus. Moreover, the text describes somatic symptoms used in the evidentiary proceedings in the case of loss of virginity and leading to the accused woman’s isolation.